Problem-based learning in facilities planning: a pilot implementation - Mohd. Yusof, Khairiyah; Syed Hassan, Syed Ahmad Helmi; Abd. Hamid, Mohd. Kamaruddin; Hassim, Mimi Haryani (2005)
In Universiti Teknologi Malaysia, Problem Based Learning (PBL) is proposed as an alternative to lectures in moulding engineering graduates to acquire attributes that are required to excel in today’s k-economy. To investigate if PBL is viable for undergraduates in the Faculty of Mechanical Engineering, a pilot implementation of PBL in Facilities Planning, a subject required for final year Mechanical Engineering undergraduates with specialization in Industrial Engineering was executed. With 60 students in the class, the whole syllabus of the subject was covered using three main PBL problems. PBL was conducted with the help of industrial partners: a semiconductor company, and a furniture factory. The outcome of the implementation was highly encouraging. Students were able to illustrate good understanding of the content, while progressively exhibiting maturity in their generic skills, such as communication, team-working, self-directed learning and problem-solving. However, several aspects of the execution can be further improved.